THE EFFECT OF CONSUMER PRICE INDEX AND EXCHANGE RATE ON NET ASSET VALUE OF SHARIA MUTUAL FUNDS IN INDONESIA IN 2019-2023 - Nikaso, Flora (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study examines the impact of macroeconomic factors, specifically the Consumer Price Index (CPI) and exchange rates, on the performance of Islamic mutual funds from 2019 to 2023. Data was sourced from the Financial Services Authority (OJK) for Islamic mutual fund net asset values (NAV) and the Central Statistics Agency (BPS) for CPI and exchange rate data. The analysis was conducted using the Vector Error Correction Model (VECM) with e-views 12 SV software. The results show that the CPI significantly affects the NAV of Islamic mutual funds in the long term, with a t-statistic value of 4.05228, higher than the t-table value of 2.0024655. Similarly, the exchange rate also impacts on NAV with a t-statistic of 7.02911, which is greater than the t-table value. In the short term, however, the CPI (t-statistic value 0.91235) and exchange rate (t-statistic value 0.96057) do not significantly influence the NAV. These findings suggest that while exchange rates and inflation may not have an immediate effect, they can impact Islamic mutual funds' NAV in the long run. Investment managers should consider adjusting strategies by selecting inflation-resistant assets or diversifying portfolios based on long-term economic trends.